Practice patterns, techniques, and outcomes of flexible endoscopic myotomy for Zenker’s diverticulum: a retrospective multicenter study - Mittal, Chetan; Diehl, David L.; Draganov, Peter V.; Jamil, Laith H.; Khalid, Ammara; Khara, Harshit S.; Khullar, Vikas; Law, Ryan; Lo, Simon K.; Mathew, Abraham; Mirakhor, Ebrahim; Sedarat, Alireza; Sharma, Neil; Sharzehi, Setareh; Tavakkoli, Anna; Thaker, Adarsh; Thosani, Nirav; Yang, Dennis; Zelt, Christina; Wagh, Mihir S. (Endoscopy, 2020)
Background Flexible endoscopic myotomy has been increasingly performed for Zenker’s diverticulum using various endoscopic techniques and devices. The main aims of this study were to assess practice patterns and compare outcomes of endoscopic myotomy for Zenker’s diverticulum.Methods Procedures performed at 12 tertiary endoscopy centers from 1/2012 to 12/2018 were reviewed. Patients (≥ 18 years) with Zenker’s diverticulum who had dysphagia and/or regurgitation and underwent endoscopic myotomy were included. Outcomes assessed included technical success, clinical success, and adverse events.Results 161 patients were included. Traditional endoscopic septotomy was performed most frequently (137/161, 85.1 %) followed by submucosal dissection of the septum and myotomy (24/161, 14.9 %). The hook knife (43/161, 26.7 %) and needle-knife (33/161, 20.5 %) were used most frequently. Overall, technical and clinical success rates were 98.1 % (158/161) and 78.1 % (96/123), respectively. Adverse events were noted in 13 patients (8.1 %). There was no significant difference in technical and clinical success between traditional septotomy and submucosal dissection groups (97.1 % vs. 95.8 %, P = 0.56 and 75.2 % vs. 90.9 %, P  = 0.16, respectively). Clinical success was higher with the hook knife (96.7 %) compared with the needle-knife (76.6 %) and insulated tip knife (47.1 %). Outcomes were similar between centers performing > 20, 11 – 20, and ≤ 10 procedures.Conclusions Flexible endoscopic myotomy is an effective therapy for Zenker’s diverticulum, with a low rate of adverse events. There was no significant difference in outcomes between traditional septotomy and a submucosal dissection approach, or with centers with higher volume, though clinical success was higher with the hook knife.